Preparation method and application of biomass-based hard carbon negative electrode material meeting fast charging
By using mosaic bamboo powder and red phosphorus or red phosphorus-sulfur powder blending method, a red phosphorus composite hard carbon material was prepared, which solved the problem of insufficient sodium ion utilization rate and serious capacity attenuation during the first charge and discharge of the hard carbon anode material of sodium ion battery during the first charge and discharge process, and achieved efficient and low-cost hard carbon anode material preparation.
Patent Information
- Application Number
- CN202510178649.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-25
AI Technical Summary
The existing sodium ion battery hard carbon anode materials have insufficient sodium ion utilization during the first charging and discharge process, and the capacity attenuation is severe, especially in low temperature and high-speed cycle scenarios, and the production process is complex and costly.
Mosaic bamboo powder is used as the hard carbon precursor, and the red phosphorus composite hard carbon material is prepared by high-temperature carbonization and blending with red phosphorus or red phosphorus-sulfur powder, followed by vacuum sealing and muffle furnace insulation.
The first Coulomb efficiency and rate performance of hard carbon anode materials have been improved, the preparation cost has been reduced, and the preparation plan for commercially used hard carbon anode materials for sodium ion batteries has been expanded.
Smart Images

Figure CN119873797A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery electrode materials, and relates to a preparation method and application of a biomass-based hard carbon negative electrode material that meets the requirements of fast charging. Background Art
[0002] Similar to lithium-ion intercalation chemistry batteries, sodium-ion batteries (SIBs) are expected to become an alternative solution for grid-scale energy storage systems and low-speed electric vehicles due to the abundant natural reserves of sodium resources and their lower price than lithium. The development of high-performance, low-cost electrode materials is the key to the large-scale commercialization of sodium-ion batteries. For negative electrode materials, hard carbon (HC) is widely used due to its easily accessible precursor resources, abundant sodium storage sites, and convenient Na + The larger interlayer spacing of diffusion makes it the first choice for SIB negative electrode materials.
[0003] However, in practical applications, HC negative electrodes still have problems such as insufficient sodium ion utilization and severe capacity decay during the first charge and discharge process, especially in low-temperature operation scenarios and high-rate cycles. In order to achieve stable cycles at high rates and rapid charge and discharge, current research is mainly focused on improving rate performance by designing alloyed negative electrode materials. However, the inherent volume expansion and structural instability during the cycle seriously affect safety. At the same time, the high cost of alloyed negative electrode materials is also increasing the cost of using batteries.
[0004] Therefore, a lower-cost and more universal hard carbon modification process route is needed to solve the above-mentioned technical problems and ultimately achieve efficient preparation of hard carbon negative electrodes with fast charging performance. Summary of the invention
[0005] The present invention is based on biomass-based hard carbon materials, which have a wide range of sources, low costs, and mature processes to become a good base model material for modifying the negative electrode to achieve fast charging. In order to achieve fast charging performance, the academic community has proposed two modification strategies. One strategy is to adjust the physical structure of the carbonaceous material, including the rational design of the pore structure. This synthesis strategy can obtain more ion channels, increase the specific surface area, and provide a sufficient microscopic environment for the diffusion and storage of sodium ions, thereby improving the electrochemical performance of SIBs. The other is to coat the surface of the negative electrode hard carbon material to achieve irreversible sodium storage sites on the carbon surface and improve the first coulomb efficiency; at the same time, the coating layer can react with sodium to construct an inorganic component-rich SEI with good sodium ion conductivity and high Young's modulus, which can improve the fast charging performance while avoiding the formation of sodium dendrites during fast charging.
[0006] The present invention addresses the problems of low initial efficiency and poor fast charging performance of existing sodium ion battery hard carbon negative electrodes, as well as complicated production and preparation processes and high costs. By using bamboo powder as a hard carbon precursor, after a high-temperature calcination, the carbonized material is blended with red phosphorus powder or red phosphorus-sulfur powder in a certain proportion and fully ground, and then transferred to a glass tube for vacuum sealing, and then quickly cooled and cooled after insulation treatment in a muffle furnace to obtain a red phosphorus composite hard carbon material. In summary, the obtained hard carbon material can achieve an increase in the first coulomb efficiency and an improvement in the rate performance, while greatly reducing the preparation cost of high-performance hard carbon materials, further expanding the preparation scheme of commercial hard carbon negative electrode materials for sodium ion batteries.
[0007] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing a biomass-based hard carbon negative electrode material that meets fast charging requirements, comprising the following steps:
[0008] Step 1: drying the bamboo powder in an environment of 50-80°C for not less than 8 hours, then carbonizing the dried bamboo powder under the protection of an inert gas at a high temperature, heating the temperature to 1000-1300°C at a rate of 1-5°C / min and keeping the temperature for 1-5 hours, and grinding the bamboo powder after the high-temperature carbonization after natural cooling to obtain a bamboo powder-based hard carbon material;
[0009] Step 2: mixing the bamboo powder-based hard carbon material obtained in step 1 with red phosphorus powder and grinding them, and then subjecting the ground mixture to a vacuum sealing treatment;
[0010] Alternatively, the bamboo powder-based hard carbon material obtained in step 1 is mixed with red phosphorus powder and sulfur powder and then ground, and then the ground mixture is subjected to vacuum sealing treatment;
[0011] Step 3: calcining the vacuum sealed tube treated hard carbon material obtained in step 2 at a heating rate of 3-10°C / min and a temperature of 200-450°C for 2-5 hours;
[0012] Step 4: After the calcination and heat preservation, the vacuum sealed tube treated hard carbon material is naturally cooled to 200-280° C., and then the tube is cut and collected to obtain the hard carbon negative electrode material.
[0013] Preferably, in step 2, when the bamboo powder-based hard carbon material and the red phosphorus powder are mixed and ground, the amount of red phosphorus used accounts for 5wt%-20wt% of the mass of the bamboo powder-based hard carbon material, and the grinding time is 0.5-2h.
[0014] Preferably, in step 2, when the bamboo powder-based hard carbon material is mixed with red phosphorus powder and sulfur powder for grinding, the amount of red phosphorus used accounts for 5wt%-20wt% of the mass of the bamboo powder-based hard carbon material, the amount of sulfur used accounts for 1wt%-5wt% of the mass of the bamboo powder-based hard carbon material, and the grinding time is 0.75-2.5h.
[0015] More preferably, in step 2, when the bamboo powder-based hard carbon material is mixed with red phosphorus powder and sulfur powder for grinding, the sulfur powder and the bamboo powder-based hard carbon material are first ground for 0.25-0.5h, and then the red phosphorus powder is added and the grinding and mixing is continued for 0.5-2h.
[0016] Preferably, the inert gas in step 1 is selected from one of argon, nitrogen and helium.
[0017] Preferably, the drying equipment in step 1 includes an oven, and the high-temperature carbonization equipment includes a tubular furnace;
[0018] The vacuum tube sealing processing equipment in step 2 includes a vacuum sealer;
[0019] The calcining equipment in step 3 includes a muffle furnace.
[0020] The present invention also discloses an application of a biomass-based hard carbon negative electrode material that meets the requirements of fast charging. The application adopts the hard carbon negative electrode material prepared by the above-mentioned preparation method, and the application uses the hard carbon negative electrode material to prepare a negative electrode for a sodium ion battery.
[0021] Preferably, the preparation method of the sodium ion battery negative electrode comprises: mixing the hard carbon negative electrode material with Super-P and polyvinylidene fluoride PVDF in a mass ratio of 80:5-15:5-15, adding N-methylpyrrolidone NMP and grinding to form a slurry, and then evenly coating the slurry on a carbon-coated aluminum foil current collector, and vacuum drying at 50-70°C for 10-14h, and then cutting it into a sodium ion battery negative electrode sheet.
[0022] More preferably, the preparation method of the sodium ion battery includes: transferring the prepared sodium ion battery negative electrode sheet into a glove box, using metallic sodium as the counter electrode, dissolving NaPF6 in ethylene carbonate EC and diethyl carbonate DEC solution and adding fluoroethylene carbonate FEC additive as the electrolyte, and assembling into a button battery.
[0023] The beneficial effects of the present invention are:
[0024] The present invention aims to solve the problems of low initial efficiency and poor high-rate rapid charge and discharge performance of hard carbon negative electrode materials. A uniform phosphating layer is constructed on the surface of the hard carbon negative electrode materials through a composite red phosphorus process, which can react with sodium to form a more Na3P-rich SEI during the first charge and discharge process, thus achieving a lower Na + Desolvation barrier and faster Na + Through the diffusion ability of SEI, efficient preparation of high-performance and low-cost biomass-based hard carbon materials can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1This is a scanning electron microscope (SEM) comparison diagram of a preparation method and application of a biomass-based hard carbon negative electrode material that meets the requirements of fast charging according to the present invention;
[0026] Figure 2 X-ray diffraction (XRD) diagrams of the hard carbon materials prepared in Examples 1, 2, 3 of the present invention and Comparative Example 1;
[0027] Figure 3 The Raman spectra of the hard carbon materials prepared in Examples 1, 2, 3 of the present invention and Comparative Example 1;
[0028] Figure 4 This is an X-ray photoelectron spectroscopy (XPS) diagram of the hard carbon material prepared in an embodiment of the present invention;
[0029] Figure 5 The rate performance diagram of the hard carbon materials prepared in Examples 1, 2, 3 of the present invention and Comparative Example 1;
[0030] Figure 6 The rate performance diagram of the hard carbon material prepared in Examples 4, 5 and 6 of the present invention;
[0031] Figure 7 The rate performance diagram of the hard carbon material prepared in Examples 7, 8 and 9 of the present invention;
[0032] Figure 8 The rate performance diagram of the hard carbon material prepared in Examples 10, 11, and 12 of the present invention;
[0033] Fig. 9 Cyclic performance diagram of the hard carbon materials prepared in Examples 1, 2, 3 of the present invention and Comparative Example 1 at 0.2C and 4C. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the relevant technologies in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In one aspect, the present invention provides a method for preparing a sodium ion battery resin-based hard carbon negative electrode, comprising the following steps:
[0036] Step 1: Dry the bamboo powder in an oven overnight, then weigh a certain mass of the bamboo powder, put it into a corundum boat and place it in a tubular furnace, and carbonize it at high temperature under the protection of an inert gas. During high-temperature carbonization, the heating rate is 1-5°C / min, and the powder is kept warm at a certain pyrolysis temperature; the powder is naturally cooled and then ground to obtain a bamboo powder-based hard carbon material.
[0037] Step 2: Grind the bamboo powder-based hard carbon material obtained in step 1 with red phosphorus powder in a certain mass ratio for a certain period of time, and then transfer them to a vacuum sealing machine for vacuum sealing.
[0038] Step 3, grinding the bamboo powder-based hard carbon material obtained in step 1 with red phosphorus powder and sulfur powder in a certain mass ratio for a certain period of time, and then transferring it to a vacuum sealing machine for vacuum sealing treatment.
[0039] Step 4, sealing the hard carbon material after blending with red phosphorus or red phosphorus-sulfur powder and transferring it to a muffle furnace, and performing heat preservation treatment under the vacuum state created by the sealing tube.
[0040] Step 5, after the insulation is completed, the cover of the muffle furnace that has naturally cooled to a specific temperature is opened to allow it to quickly cool to room temperature, and then the tube cutting operation is performed in a fume hood to collect hard carbon materials with different degrees of phosphating.
[0041] As in the preparation method described above, in step one, the oven is placed at a drying temperature of 50-80°C, the carbonization temperature in the inert atmosphere of the tube furnace is 1000-1300°C, the inert gas is selected from one of argon, nitrogen, and helium, and the high-temperature carbonization maintenance time is 1-5h.
[0042] As in the above-mentioned preparation method, in step 2, the amount of red phosphorus used is 5wt%-20wt% of the mass of the bamboo powder-based hard carbon material, and the grinding time is controlled to be 0.5-2h.
[0043] As in the preparation method described above, in step three, the amount of sulfur powder used is 1wt%-5wt% of the mass of the bamboo powder-based hard carbon material. After the two are fully ground for 0.25-0.5h, red phosphorus in the required proportion in step two is added, and the grinding and mixing are continued for 0.5-2h.
[0044] As in the above-mentioned preparation method, in step 4, the heating rate in the muffle furnace is 3-10°C / min, the temperature is maintained at 200-450°C, and the insulation time is 2-5h.
[0045] As in the above preparation method, in step 5, after the heat preservation is completed, the temperature is naturally lowered to 200-280°C, and the lid of the muffle furnace is opened to rapidly cool it to room temperature. The composite hard carbon materials obtained by heat preservation of different red phosphorus or red phosphorus-sulfur powder and hard carbon blend materials in step 2 and step 3 are named HC-X%P and HC-X%SX%P respectively (as listed in Table 1).
[0046] On the other hand, the present invention provides a sodium ion battery biomass-based hard carbon negative electrode material prepared by the above method and a negative electrode prepared from the above sodium ion battery biomass-based hard carbon negative electrode material.
[0047] refer to Figures 1 to 9 The technical solution claimed to be protected by the present invention is further described below through the accompanying drawings and embodiments.
[0048] Example 1
[0049] This example is used to illustrate the preparation, physical structure and electrochemical performance of biomass-based hard carbon materials for sodium ion batteries that meet the requirements of fast charging of the present invention; it includes the following steps:
[0050] (1) 1 g of bamboo powder was spread evenly in a corundum boat and placed in a 60°C forced air oven for 10 h to dry. After drying, it was transferred to a corundum tube furnace and heated to 1100°C at a rate of 5°C / min under 200 SCCM argon protection for 4 h. After cooling naturally, the obtained hard carbon was further ground into fine powder;
[0051] (2) Weigh 200 mg of the hard carbon material prepared in step (1) and place it in an agate mortar, then weigh 10 mg of red phosphorus and add it to the mortar, and grind the two for 30 minutes until the powder is uniform in color and appears dark brown overall;
[0052] (3) The powder in step (2) is transferred to a glass tube with a shrunken neck, and the tube is sealed using a vacuum tube sealer. The successfully sealed glass tube is placed in a muffle furnace, and the temperature is raised to 450° C. at a heating rate of 5° C. / min for 5 hours.
[0053] (4) Wait for the glass tube that has been heat-insulated in step (3) to naturally cool to 200°C in the closed muffle furnace, then open the furnace cover, take it out using heat-insulating gloves, and place it in a fume hood to quickly cool to room temperature. Cut the tube and collect the composite hard carbon material.
[0054] (5) The composite hard carbon material obtained in step (4) is mixed evenly with Super-P and polyvinylidene fluoride (PVDF) in a mass ratio of 80:10:10, and an appropriate amount of N-methylpyrrolidone (NMP) is added and ground into a slurry, and then the slurry is evenly coated on the carbon-coated aluminum foil current collector, and after vacuum drying at 60°C for 12 hours, it is cut into a circular electrode with a diameter of 12 mm;
[0055] (6) The hard carbon negative electrode obtained in step (5) was transferred to a glove box, and sodium metal was used as the counter electrode. 1 mol of NaPF6 was dissolved in 1L of ethylene carbonate (EC) and diethyl carbonate (DEC) solution with a volume ratio of 1:1 and 5% fluoroethylene carbonate (FEC) additive was added as the electrolyte to assemble a CR2032 button cell. Charge and discharge tests were performed at different rates of 0.1C-4C, and long cycle charge and discharge tests were performed at rates of 0.2C, 4C and 10C, with a charge and discharge voltage cutoff interval of 0-3V.
[0056] Figure 1 Including the SEM image of the hard carbon material prepared in this example, it can be seen from the image that the surface of the phosphating hard carbon in Example 1 has certain protrusions, and the size of the blocks is about 25 μm. Figure 2 The XRD spectrum shows two broad diffraction peaks at 23° and 43°, which correspond to the (002) and (100) crystal planes, respectively. It can be seen that compared with the comparative example 1-bamboo powder hard carbon, the peak position of the 002 plane has shifted to the left, indicating that the interlayer spacing of the graphite microcrystals has also increased with the phosphating process. The overall structure is low-graphitization amorphous, belonging to amorphous carbon materials. Figure 3 is the Raman spectrum, and the I representing the degree of graphitization is calculated. D / I G The value is 2.14, and the surface defects are larger than those in Comparative Example 1. Figure 5 The rate test shows that the rate capacity retention rate of Example 1 at 0.1-4C is 78.9%. This is significantly higher than the 64.3% of Comparative Example 1. This preliminarily shows that the phosphating treatment to prepare the composite material helps improve the fast charging performance. Further cycle stability tests at 0.2C and 4C show that Fig. 9 It can be seen that the reversible charge capacity of the phosphating composite material is greatly improved compared with that of comparative example 1. In particular, after 1000 cycles at 4C, the capacity of Example 1 is 184-162 mAh / g, with a retention rate of 88%; the capacity of comparative example 1 is 187-140 mAh / g, with a retention rate of 74.8%.
[0057] Example 2
[0058] The difference from Example 1 is that the amount of red phosphorus in the above step (2) is adjusted to 20 mg, added to an agate mortar, and the two are fully ground for 1 hour until the powder color is uniform and the whole is dark brown.
[0059] The subsequent steps are the same as (3), (4), (5) and (6) in Example 1, except that the hard carbon material obtained in (3) is named Example 2.
[0060] Figure 1 Including the SEM image of the hard carbon material prepared in Example 2, as the quality of red phosphorus improves, the protrusions on the hard carbon surface further increase, indicating that a certain degree of agglomeration occurs in the phosphating process. Figure 2 From the XRD spectrum, it can be seen that compared with comparative example 1, the degree of graphitization is reduced, and the interlayer spacing of the 002 crystal plane also shows an increasing trend, which also belongs to an amorphous carbon material. Figure 3 is the Raman spectrum, and the I representing the degree of graphitization is calculated. D / I G The value is 2.03, which is consistent with the XRD results analysis. Compared with HC, the degree of carbon skeleton defects increases. Figure 4This is the XPS spectrum of Example 2, including the overall spectrum and the fine spectra of C1s and P2p. From the formation of PC bonds, it can be seen that since the temperature of the subsequent sealing and insulation process is higher than the phase transformation temperature of red phosphorus, a part of the vaporized phosphorus reacts with carbon to form PC bonds, which are strongly bound to the carbon surface and the main body. Figure 5 For the rate performance test, Example 2 showed the highest reversible capacity of 281-218 mAh / g at 0.1C-4C, and the capacity retention rate was 77.6%. Fig. 9 The 0.2C and 4C cycle stability tests show that Example 2 exhibits the highest reversible capacity. The 100-cycle capacity at 0.2C is 264-257mAh / g, and the capacity retention rate is 97.3%, which is an excellent performance. At the same time, the 1000-cycle capacity retention rate at 4C is 84% (207-174mAh / g). The stable electrochemical performance, combined with the physical characterization analysis, shows that as the phosphating proceeds, the surface and body of the bamboo powder hard carbon material are both compounded with phosphorus. During the first discharge process, sodium ions can react with the phosphating layer on the surface to achieve a SEI with a high proportion of Na3P. This component structure is beneficial for shielding the subsequent electrolyte side reactions. At the same time, it can stabilize the interface layer at a higher current density, and jointly promote the performance of the battery under high-rate charge and discharge, providing a feasible preparation process for the commercial application of biomass-based hard carbon materials.
[0061] Example 3
[0062] The difference from Example 1 is that the amount of red phosphorus in step (2) is adjusted to 40 mg, added to an agate mortar, and the two are fully ground for 1 hour until the powder color is uniform and the whole is dark red.
[0063] The subsequent steps are the same as (3), (4), (5) and (6) in Example 1, except that the hard carbon material obtained in (3) is named Example 3.
[0064] Figure 1 Including the SEM image of the composite hard carbon material prepared in this embodiment, it can be found that due to the further increase in the amount of red phosphorus used, the hard carbon surface has been covered with a layer of particles of different sizes, and the apparent roughness has increased. Figure 2 XRD and Figure 3 From the Raman results, it can be seen that the degree of surface defects is increased compared with Examples 1 and 2 and Comparative Example 1, and the interlayer spacing of the graphite microcrystals is further increased. Figure 5 The rate test results show that further increasing the amount of red phosphorus does not lead to an optimization of the rate performance. The reversible capacity of 0.1C-4C is 276-218mAh / g, which is comparable to the performance of Example 2. Fig. 9The cycle stability test shows that Example 3 has the best 1000 cycle performance of 214-184 mAh / g at 4C, and the capacity retention rate is 85.9%. Compared with Comparative Example 1 (74.8%), it has been greatly improved; it shows that the phosphating process implemented in this method has a high practical production significance for preparing a fast-charging biomass-based sodium-ion battery hard carbon negative electrode.
[0065] Example 4
[0066] The difference from Example 1 is that in step (2), 2 mg of sulfur powder is first added to the hard carbon material and fully ground for 15 minutes, then 10 mg of red phosphorus is added to an agate mortar and the two are fully ground for 30 minutes until the powder color is uniform and the whole is gray.
[0067] The subsequent steps are the same as (3), (4), (5) and (6) in Example 1, except that the hard carbon material obtained in (3) is named Example 4.
[0068] Example 5
[0069] The difference from Example 4 is that the mass of sulfur powder used is 2 mg, the mass of red phosphorus used is adjusted to 20 mg, and the two are fully ground for 1 hour until the powder color is uniform. The other operations remain unchanged, and the hard carbon material obtained is named Example 5.
[0070] Example 6
[0071] The difference from Example 4 is that the mass of red phosphorus used in step (2) is adjusted to 40 mg, the mass of sulfur powder used is still 2 mg, and it is fully ground with the hard carbon material for 1 hour, and the other operations remain unchanged. The obtained hard carbon material is named Example 6.
[0072] Figure 6 The test data of the rate performance of Examples 4, 5, and 6 are shown. Considering that the phosphating of Examples 1, 2, and 3 is not sufficient, a certain mass percentage of sulfur powder (1wt%) is added during the phosphating process with reference to existing work reports, and sulfur is used as a medium for carbon-based bridging phosphorus to promote the phosphating process. The results show that the rate capacity retention rates of Examples 4, 5, and 6 are 71.6%, 74.6%, and 70.8%, respectively; they are all improved compared to bamboo powder hard carbon, but the rate performance of Examples 1, 2, and 3 has not been further improved.
[0073] Example 7
[0074] The difference from Example 4 is that the mass of sulfur powder used in step (2) is adjusted to 6 mg, and 10 mg of red phosphorus is added after fully grinding with the hard carbon material for 15 minutes, and the other operations remain unchanged. The obtained hard carbon material is named Example 7.
[0075] Example 8
[0076] The difference from Example 7 is that the mass of sulfur powder used is unchanged at 6 mg, the mass of red phosphorus used in step (2) is adjusted to 20 mg, and it is fully ground with the hard carbon material for 1 hour, and the other operations remain unchanged. The obtained hard carbon material is named Example 8.
[0077] Example 9
[0078] The difference from Example 7 is that only the mass of red phosphorus used is adjusted to 40 mg, and the two are fully ground for 1 hour until the powder color is uniform. The other operations remain unchanged, and the obtained hard carbon material is named Example 9.
[0079] Figure 7 The rate performance test data of Examples 7, 8, and 9, further increasing the mass proportion of sulfur powder (3wt%) in phosphating. The results show that the rate capacity retention rates of Examples 7, 8, and 9 are 70.7%, 69.4%, and 30.4%, respectively, indicating that the increase in sulfur powder and the weakened synergistic effect of red phosphorus have become an unfavorable factor affecting the reversible capacity.
[0080] Example 10
[0081] The difference from Example 4 is that the mass of sulfur powder used in step (2) is adjusted to 10 mg, and 10 mg of red phosphorus is added after fully grinding with the hard carbon material for 30 minutes, and the other operations remain unchanged. The obtained hard carbon material is named Example 10.
[0082] Embodiment 11
[0083] The difference from Example 10 is that the mass of sulfur powder used is unchanged at 10 mg, the mass of red phosphorus used in step (2) is adjusted to 20 mg, and it is fully ground with the hard carbon material for 1 hour, and the other operations remain unchanged. The obtained hard carbon material is named Example 11.
[0084] Example 12
[0085] The difference from Example 10 is that the mass of red phosphorus used is adjusted to 40 mg, and the two are fully ground for 1 hour until the powder color is uniform. The other operations remain unchanged, and the obtained hard carbon material is named Example 12.
[0086] Figure 8The rate performance test data of Examples 10, 11, and 12 further increased the mass proportion of sulfur powder (5wt%) in the phosphating process. The results show that the rate capacities 0.1C-4C of Examples 10, 11, and 12 are 231-159mAh / g, 226-161mAh / g, and 233-127mAh / g, respectively, with retention rates of 69%, 71.9%, and 54.5%, respectively; indicating that the further increase of sulfur powder will cause more serious side reactions. Based on the analysis of the above embodiments, the optimal process for achieving fast charging for the bamboo powder hard carbon negative electrode is the operation involved in Example 2.
[0087] Comparative Example 1
[0088] 1g of bamboo powder was spread evenly in a corundum boat, and placed in a 60°C forced air oven for 10 hours of drying. After drying, it was transferred to a corundum tube furnace, and heated to 1100°C at a rate of 5°C / min under 200SCCM argon protection for 4 hours, and then naturally cooled to further grind the obtained hard carbon into fine powder; the obtained material was named Comparative Example 1.
[0089] Figure 1 Including the SEM image of bamboo powder hard carbon in comparative example 1, it can be seen from the image that the surface of bamboo powder hard carbon is clean and there are certain mesoscopic pores, which provides a base material for subsequent phosphating experiments.
[0090]
[0091] Table 1 shows the experimental parameters and electrochemical properties of Examples 1-12 and Comparative Example 1. As can be seen from Table 1, the natural sulfur contained in bamboo powder hard carbon as a biomass-based hard carbon can meet the phosphating requirements. As the amount of red phosphorus used in phosphating increases, it can be seen from the physical structure analysis of Examples 1, 2, and 3 above that the surface and body of the bamboo powder hard carbon material both achieve phosphorus recombination. This also promotes the reaction of sodium ions with the phosphating layer on the surface during the first discharge process, achieving a higher proportion of the Na3P component in the SEI. This component structure is conducive to shielding the occurrence of subsequent electrolyte side reactions. At the same time, it can stabilize the interface layer at a higher current density, and jointly promote the performance of the battery under high-rate charge and discharge. In the 0.1C-4C rate performance test, the best capacity retention rate of 78.9% is shown in Example 3 (276-218mAh / g); the 1000-cycle cycle capacity at 4C is maintained at 214-184mAh / g, and the retention rate is 85.9%. The above Examples 2 and 3 provide an ideal reference for the commercial application of biomass-based hard carbon materials.
[0092] In this embodiment, the preparation process of the hard carbon material is simple and efficient, the composite utilization efficiency of red phosphorus is high, and low-cost and large-scale preparation can be achieved. The surface morphology of the hard carbon negative electrode is irregular block-shaped, and the microstructure is a pore structure in which micropores and mesopores coexist; this structure is a staggered stack of low-graphitization amorphous microcrystals; the hard carbon material has the ability to maintain good wettability with ester electrolytes; and as the degree of composite surface defects of red phosphorus decreases, irreversible sodium loss can be reduced.
[0093] The hard carbon material uses bamboo powder as a precursor. It is first carbonized in an inert atmosphere in a tubular furnace, then blended and ground evenly with red phosphorus or a mixture of red phosphorus and sulfur powder, resulting in a uniform powder color. It is then transferred to a shrinking test tube for vacuum sealing. The sealed test tube is then heat treated at a certain temperature in a muffle furnace. After the temperature drops rapidly, the tube is cut and the resulting carbon material is collected for subsequent pulping processes. The red phosphorus composite state of the hard carbon material is related to the amount of red phosphorus used and the ratio of red phosphorus-sulfur powder blending.
[0094] The amount of red phosphorus used greatly affects the composite effect with hard carbon. Its amount is a certain ratio of the mass of the hard carbon material. The result of red phosphorus-sulfur powder blending and hard carbon composite is also affected by their mass ratio.
[0095] In summary, the present invention aims to solve the problems of low initial efficiency and poor high-rate rapid charge and discharge performance of hard carbon negative electrode materials. A uniform phosphating layer is constructed on the surface of the hard carbon negative electrode materials through the process of composite red phosphorus, which can react with sodium to form a SEI richer in Na3P during the first charge and discharge process, thus helping to achieve a lower Na + Desolvation barrier and faster Na + Through the diffusion ability of SEI, efficient preparation of high-performance and low-cost biomass-based hard carbon materials can be achieved.
[0096] It should be emphasized that the above are only preferred embodiments of the present invention and do not impose any form of limitation on the present invention. Any simple modification of the above embodiments based on the technical essence of the present invention also falls within the protection scope of the present invention. Other equivalent changes and modifications still fall within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a biomass-based hard carbon negative electrode material that meets fast charging requirements, characterized in that: The following steps are involved: Step 1: drying the bamboo powder in an environment of 50-80°C for not less than 8 hours, then carbonizing the dried bamboo powder under the protection of an inert gas at a high temperature, heating the temperature to 1000-1300°C at a rate of 1-5°C / min and keeping the temperature for 1-5 hours, and grinding the bamboo powder after the high-temperature carbonization after natural cooling to obtain a bamboo powder-based hard carbon material; Step 2: mixing the bamboo powder-based hard carbon material obtained in step 1 with red phosphorus powder and grinding them, and then subjecting the ground mixture to a vacuum sealing treatment; Alternatively, the bamboo powder-based hard carbon material obtained in step 1 is mixed with red phosphorus powder and sulfur powder and then ground, and then the ground mixture is subjected to vacuum sealing treatment; Step 3: calcining the vacuum sealed tube treated hard carbon material obtained in step 2 at a heating rate of 3-10°C / min and a temperature of 200-450°C for 2-5 hours; Step 4: After the calcination and heat preservation, the vacuum sealed tube treated hard carbon material is naturally cooled to 200-280° C., and then the tube is cut and collected to obtain the hard carbon negative electrode material.
2. The method for preparing a biomass-based hard carbon negative electrode material that meets fast charging requirements according to claim 1, characterized in that: In the step 2, when the bamboo powder-based hard carbon material and the red phosphorus powder are mixed and ground, the amount of red phosphorus used accounts for 5wt%-20wt% of the mass of the bamboo powder-based hard carbon material, and the grinding time is 0.5-2h.
3. The method for preparing a biomass-based hard carbon negative electrode material that meets fast charging requirements according to claim 1, characterized in that: In the step 2, when the bamboo powder-based hard carbon material is mixed with red phosphorus powder and sulfur powder for grinding, the amount of red phosphorus used accounts for 5wt%-20wt% of the mass of the bamboo powder-based hard carbon material, the amount of sulfur used accounts for 1wt%-5wt% of the mass of the bamboo powder-based hard carbon material, and the grinding time is 0.75-2.5h.
4. The method for preparing a biomass-based hard carbon negative electrode material that meets fast charging requirements according to claim 3, characterized in that: In step 2, when the bamboo powder-based hard carbon material is mixed with red phosphorus powder and sulfur powder for grinding, the sulfur powder and the bamboo powder-based hard carbon material are first ground for 0.25-0.5h, and then the red phosphorus powder is added and the grinding and mixing is continued for 0.5-2h.
5. The method for preparing a biomass-based hard carbon negative electrode material that meets fast charging requirements according to claim 1, characterized in that: In step 1, the inert gas is selected from one of argon, nitrogen and helium.
6. The method for preparing a biomass-based hard carbon negative electrode material that meets fast charging requirements according to claim 1, characterized in that: The drying equipment in step 1 includes an oven, and the high-temperature carbonization equipment includes a tubular furnace; The vacuum tube sealing processing equipment in step 2 includes a vacuum sealer; The calcining equipment in step 3 includes a muffle furnace.
7. An application of a biomass-based hard carbon negative electrode material that meets fast charging requirements, characterized in that: The application adopts the hard carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 6, and the application uses the hard carbon negative electrode material to prepare the negative electrode of a sodium ion battery.
8. The use of a biomass-based hard carbon negative electrode material that meets the requirement of fast charging according to claim 7, characterized in that: The preparation method of the sodium ion battery negative electrode comprises: mixing a hard carbon negative electrode material with Super-P and polyvinylidene fluoride (PVDF) in a mass ratio of 80:5-15:5-15, adding N-methylpyrrolidone (NMP) and grinding to form a slurry, then uniformly coating the slurry on a single-sided carbon-coated aluminum foil current collector, vacuum drying at 50-70° C. for 10-14 hours, and then cutting into a sodium ion battery negative electrode sheet.
9. The use of a biomass-based hard carbon negative electrode material that meets the requirement of fast charging according to claim 8, characterized in that: The preparation method of the sodium ion battery comprises: transferring the prepared sodium ion battery negative electrode sheet into a glove box, using metallic sodium as a counter electrode, dissolving NaPF6 in ethylene carbonate EC and diethyl carbonate DEC solution and adding fluoroethylene carbonate FEC additive as an electrolyte, and assembling into a button battery.
Citation Information
Cited By
A sodium ion battery coated hard carbon material and a preparation method thereof
CN122748608A